Investigating the content of mathematics textbook used in 8th grade in Malaysia based on content domain of TIMSS - Lessani, Abdolreza; Md Yunus, Aida Suraya; Ahmad Tarmiz, Rohani; Mahmud, Rosnaini (Contemporary Research Center, 2014)
The purpose of this study is to investigate the content of Mathematics Textbook in Secondary schools 8th grade(Form 2) in Malaysia, based on content domain of TIMSS .The reason of this study is to indicate that although the average score of students were usually more than International average score, it is lower than South East Asian Countries like Japan, Singapore, south Korea Hong Cong chains Tape. We identified two main reasons for this lack of performance among Malaysian students. First, we revealed that, as compared to the base content of TIMSS, mathematic textbook (Form 2) has some lack of richness. We also revealed that the change of teaching language from Bahasa Malaya to English may have affected the students’ achievement in Mathematics.